Prioritizing Public- Private Partnership Models for Public Hospitals of Iran Based on Performance Indicators - Mohammad Asghari Jaafarabadi; Ali Jannati; Hossein Jabbari Beyrami; Raana Gholamzadeh Nikjoo (Tabriz University of Medical Sciences, 2012)
Background: The present study was conducted to scrutinize Public- Private Partnership (PPP) models in public hospitals of different countries based on performance indicators in order to se-lect appropriated models for Iran hospitals.Methods: In this mixed (quantitative-qualitative) study, systematic review and expert panel hasbeen done to identify varied models of PPP as well as performance indicators. In the second stepwe prioritized performance indicator and PPP models based on selected performance indicatorsby Analytical Hierarchy process (AHP) technique. The data were analyzed by Excel 2007 andExpert Choice11 software's.Results: In quality - effectiveness area, indicators like the rate of hospital infections(100%), hospital accidents prevalence rate (73%), pure rate of hospital mortality (63%), patientsatisfaction percentage (53%), in accessibility equity area indicators such as average inpatientwaiting time (100%) and average outpatient waiting time (74%), and in financial - efficiency area,indicators including average length of stay (100%), bed occupation ratio (99%), specific incometo total cost ratio (97%) have been chosen to be the most key performance indicators. In the prioritizationof the PPP models clinical outsourcing, management, privatization, BOO (build, own,operate) and non-clinical outsourcing models, achieved high priority for various performance indicatorareas.Conclusion: This study had been provided the most common PPP options in the field of public hospitals and had gathered suitable evidences from experts for choosing appropriate PPP option for public hospitals. Effect of private sector presence in public hospital performance, based on which PPP options undertaken, will be different.